Entrepreneurial Privatization Strategies: Order of Entry and Local Partner Collaboration as Sources of Competitive Advantage - Doh, Jonathan P. (Academy of Management Review, 2000)
Jonathan P. Doh, Entrepreneurial Privatization Strategies: Order of Entry and Local Partner Collaboration as Sources of Competitive Advantage, The Academy of Management Review, Vol. 25, No. 3 (Jul., 2000), pp. 551-571